THE EFFECT OF MARKETING MIX TOWARD CUSTOMER LOYALTY - Manik, Andy Radixson; Rofiaty, Rofiaty (Jurnal Manajemen Pemasaran dan Perilaku Konsumen, 2022)
Coffee consumption in Indonesia has been growing every year from 2016 to 2021. Consumption coffee as a beverage or Ready to Drink (RTD) are increasingly significant in Indonesia specially in Coffee Shops and it is a trend in nowdays. The marketing mix should be conducted carefully as it is one of big aspects on business. This research aims to determine the effect of the marketing mix on costumer loyalty variables. This is explanatory research that explains the relationship and influence between one variable and another by submitting a hypothesis. This research used a sample of 100 respondents by online questionnaires distribution. The sample consisted of respondents who had visited Nakoa Coffee Shops in Malang. Data were analysed with multiple linear regression using the SPSS 21 program. The test results of the seven hypotheses concluded that marketing mix has a significant effect on costumer loyalty. This research is expected to become a reference for Nakoa Coffee Shops in Malang to improve and enhance their business performance in the future.